Prevalence of hepatitis B and C seropositivity in a Nigerian cohort of HIV-infected patients (2008)
"INTRODUCTION:The clinical and public health implications of the convergence of the human immunodeficiency virus (HIV) epidemic and chronic viral hepatitis in sub-Saharan Africa are poorly understood. This study was designed to determine the seroprevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV), and the impact of co-infection on baseline serum alanine transaminase (ALT), CD4+ T lymphocyte (CD4) count, and plasma HIV-RNA (viral load) in a cohort of HIV-infected Nigerians. METHODS:A retrospective study was conducted, on eligible treatment-naive patients who presented between August 2004 and February 2007 to the University College Hospital (UCH), Ibadan, Nigeria. Demographic data and pre-treatment laboratory results (hepatitis B surface antigen (HBsAg), HCV antibodies (anti-HCV), ALT, CD4 count and viral load) were retrieved from the medical records. Fisher's exact, two sample t-tests, and the Wilcoxon rank sum tests were used to compare groups. A logistic regression model was fitted to explore characteristics associated with co-infection status. RESULTS:A total of 1779 HIV-infected patients (male: female ratio, 1:2) met inclusion criteria. HBsAg was present in 11.9%, anti-HCV in 4.8% and both markers in 1%. HBsAg was more common among males than females (15.4% vs 10.1%, respectively p = 0.001) while anti-HCV was detected in a similar proportion of males and females (5.3% versus 4.6%, respectively p = 0.559). HIV-infected patients with anti-HCV alone had a lower mean baseline CD4 count compared to those without anti-HCV or HBsAg (197 cells/mm3 vs 247 cells/mm3, respectively p = 0.008). Serum ALT was higher among patients with HBsAg compared to those without HBsAg or anti-HCV (43 International Units (IU) vs. 39 IU, respectively p = 0.015). Male gender was associated with HBV co-infection on logistic regression (OR1.786; 95% CI, 1.306-2.443; p < 0.005). CONCLUSION:More HIV-infected females than males presented for care in this cohort. We identified a relatively high prevalence of HBV and HCV co-infection in general, and a higher rate of HBV co-infection among males than females. Pre-treatment CD4 count was significantly lower among those with HCV co-infection, while ALT was slightly higher among those with HBV co-infection. Triple infection with HIV, HBV and HCV was present in a small but significant proportion of patients. These findings underscore the importance of testing for HBV and HCV in all HIV-infected persons in our setting."